Joan Morgan: The Book of Pears. The Definitive History and Guide to over 500 Varieties - Pawley, Clare (Petits Propos Culinaires, 2015)
Joan Morgan: The Book of Pears. The Definitive History and Guide to over 500 Varieties: paintings by Elisabeth Dowle: Ebury Press, 2015: 304 pp., hardback, £45.